Molecular basis for CPAP-tubulin interaction in controlling centriolar and ciliary length - Xiangdong Zheng (Nature Portfolio, 2016)
Centrioles and cilia are microtubule-based structures of defined architecture, but what regulates this architecture is not clear. Here the authors discover that centrosomal-P4.1-associated-protein (CPAP) binds the α/β-tubulin dimer and licenses it for tubulin delivery contributing to centriolar/ciliary length and architecture control.